Frontline Employees’ Service Recovery Performance in Malaysian Hotels - Nik Mohd Masdek, Nik Rozana (2010)
There are many aspects in which service failures can occur, especially in a high-contact service setting. In any scenario where service failures do occur, frontline employees often play a critical role in addressing customer dissatisfaction, and this underscores the importance of examining employee’s Service Recovery Performance (SRP). Majority of past studies chose to test their model in the banking and manufacturing industries.Empirical findings within the hotel industry is seen as scarce. This study investigates a model of service recovery performance of frontline employees in the hotel industry, based on established model by Boshoff and Allen (2000). It investigates the relationship between SRP and selected organizational variables; customer service orientation, rewarding service excellence, empowerment, training, teamwork, role ambiguity and organizational commitment, as well as the impact that employees’ effective SRP may have on two identified outcome variables; job satisfaction and intentions to resign.